Recent publications on the early history of Chinese mathematics (essay review) - VOLKOV, ALEXEI (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2012)
Abstract The author discusses the earliest extant Chinese mathematical treatises, Jiu zhang suan shu九章算術 (Computational procedures of nine categories), compiled no later than the first century AD, and three recently unearthed mathematical texts, Suan shu shu筭數書 (Scripture on computations [to be performed] with counting rods), Shu 數 (Numerical [procedures (?)]), and Suan shu算術 ([Computational] Procedures [to be performed with] Counting Rods), all dated of the late first millennium BC. The main question addressed in the review is that of the origin and early history of the Jiu zhang suan shu. Some modern historians suggested that this treatise was considered a “canonical” text by its commentator of the third century, Liu Hui劉徽 (fl. AD 263). The author suggests that this claim is based solely on one phrase found in the commentator’s preface. Instead, the recent findings suggest that a number of mathematical texts were produced, copied and studied in China from the 3rd century BC onwards, and none of them had the status of a “canonical scripture”; these texts, the author suggests, most likely were used for educational purposes. Resumo O autor discorre sobre os primeiros e remanescentes tratados da matemática chinesa, Jiu zhang suan shu 九章算 (Procedimentos de conta das nove categorias), compilados não depois do primeiro século d.C., e sobre três textos matemáticos recentemente descobertos, Suan shu shu 筭數書 (Registro de contas [a serem realizadas] com barras de contar), Shu 數 ([Procedimentos (?)] numéricos), e Suan shu 算術 (Procedimentos [de contagem] [a ser realizada com] barras de contar), todos datados do final do primeiro milênio a.C. A principal questão desta revisão crítica é a origem e a história de Jiu zhang suan shu. Alguns historiadores modernos sugerem que este tratado era considerado um texto “canônico” por seu comentador do terceiro século, Liu Hui劉徽 (fl. 263 d.C.). O autor sugere, neste artigo, que essa afirmação está baseada em uma frase encontrada no prefácio do comentarista. Em vez disso, descobertas recentes sugerem que uma série de textos matemáticos foi produzida, copiada e estudada na China a partir do século 3 a.C., e nenhum desses textos tinham o estatuto de “escritura canônica”. O autor sugere que esses textos, provavelmente, eram destinados para fins educacionais.